(untitled) (Progressive Agriculture, 2013)
Random Amplified Polymorphic DNA (RAPD) assay was initiated for molecular genetic analysis among 13 F3 rice lines and their parents. Four out of 15 decamer random primers were used to amplify genomic DNA and the primers yielded a total of 41 RAPD markers of which 37 were considered as polymorphic with a mean of 9.25 bands per primer. The percentage of polymorphic loci was 90.24. The highest percentage of polymorphic loci (14.63) and gene diversity (0.0714) was observed in 05-6 F3 line and the lowest polymorphic loci (0.00) and gene diversity (0.00) was found in 05-12 and 05-15 F3 lines. So, relatively high level of genetic variation was found in 05-6 F3 line and it was genetically more diverse compared to others. The average co-efficient of gene differentiation (GST) and gene flow (Nm) values across all the loci were 0.8689 and 0.0755, respectively. The UPGMA dendrogram based on the Neis genetic distance differentiated the rice genotypes into two main clusters: PNR-519, 05-19, 05-14, 05-12 and 05-17 grouped in cluster 1. On the other hand, Baradhan, 05-9, 05-13, 05-11, 05-5, 05-6, 05-1, 05-4, 05-15 and 05-25 were grouped in cluster 2. The highest genetic distance (0.586) was found between 05-4 and 05-17 F3 lines and they remain in different cluster. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16839 Progress. Agric. 20(1 & 2): 1 8, 2009